‘My Husband Won't Tell the Children!’ - Dubler, Nancy Neveloff (The Hastings Center report, 1984)
This factual case study is one of a series demonstrating ethical dilemmas in medicine, science, the social sciences, and public policy. Although the case is based on fact, it has been edited to preserve confidentiality and to emphasize the ethical questions. Readers are invited to submit cases for consideration for this series. Case descriptions should be typed, doubled-spaced, and should not exceed 750 words.